Comparative study between ischemic compression and dry needling in myofascial pain syndrome: possibilities in health - Paula, Vanessa Renata Molinero de; Paula, Gustavo Melo de; Just, Jadson; Soares, Cláudia F.; Sanchez, Hugo Machado (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Introduction: Myofascial Pain Syndrome (MPS) is a neuromuscular regional dysfunction characterized by the presence of sensitive regions in strained muscle bands (trigger points), able to cause local and referred pain, functional losses and change the quality of life (QOL) of affected people. It can be triggered by musculoskeletal injuries, postural imbalances, endocrinal factors and psych emotional disorders. The diagnostic is clinical, the intervention is multidisciplinary and the treatment may involve the use of drugs and several invasive and non-invasive techniques. Objective: Compare the effects of ischemic compression associated to physiotherapy and dry needling associated to pain control and the QOL of people with MPS. Methods: 40 subjects took part of the study. They were of both genders, aged from 20 to 60 years old, with MPS, divided into 2 groups with 20 participants each. The first group receives ischemic compression and physiotherapy and the second, dry needling and physiotherapy. The statistical analysis involves proportions for categorical variables, significance and standard deviation for continuous variables. In order to evaluate the change in the pain and QOL perception of subjects, the Student’s t-test (p<0.05). Results: The best results were verified in the dry needling and physiotherapy group. Conclusion: Both ischemic compression and physiotherapy as dry needling and physiotherapy can promote pain relief and better QOL in subjects suffering from MPS.